EATING HABITS OF NAZARBAYEV UNIVERSITY STUDENTS: HOW HAS AN ATTITUDE TOWARDS COMMENSALITY CHANGED? - Kuanysheva, Aitolkyn (Nazarbayev University School of Sciences and Humanities, 2024)
This capstone project studies changes in the eating habits of Nazarbayev University students and their attitudes towards commensality, namely eating together, during their academic journey from the first to the last year. This study uses a qualitative research approach based on interview results conducted among students from different backgrounds. Eating habits reflect changes in students' social identities when adjusting to university. For example, in the first year, students are interested in integrating into the university's new society through communal meals. In contrast, they tend to strengthen their social connections and group identity in their senior year. The practice of sharing meals helps to strengthen social capital among students. Commensality is the opportunity to create new connections and establish mutually beneficial relationships, which influences the formation of social networks and support in the university environment. Social practices in the context of the university community reflect sociocultural norms and expectations, which explain how students interact and establish their social relationships through food. The findings may help shape cafeteria policies, organize social events, and create a supportive environment for students at the university. Additionally, the study reveals the importance of communal nutrition in forming student culture and social adaptation in the university environment. The results obtained within the project are discussed and analyzed in the context of changing perceptions and attitudes towards commensality, social relationships, and the evolution of students' eating habits.
Keywords: Type of access: Open Access; commensality; eating habits; social capital; social identity; social practices; attitude; change